2017
DOI: 10.1161/circresaha.117.310959
|View full text |Cite
|
Sign up to set email alerts
|

The Brugada Syndrome Susceptibility Gene HEY2 Modulates Cardiac Transmural Ion Channel Patterning and Electrical Heterogeneity

Abstract: Rationale: Genome-wide association studies previously identified an association of rs9388451 at chromosome 6q22.3 (near HEY2 ) with Brugada syndrome. The causal gene and underlying mechanism remain unresolved. Objective: We used an integrative approach entailing transcriptomic studies in human hearts and electrophysiological studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Genetic variants in proteins in the signaling pathways and/or transcription factors can potentially cause DI‐type 1 BrP or BrS . Loss‐of‐function mutation in Tbx5 (G145R) has been shown to cause BrS in humans .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic variants in proteins in the signaling pathways and/or transcription factors can potentially cause DI‐type 1 BrP or BrS . Loss‐of‐function mutation in Tbx5 (G145R) has been shown to cause BrS in humans .…”
Section: Discussionmentioning
confidence: 99%
“…Tbx5 and Tbx3 have been also shown to regulate the BrS susceptibility genes “SCN5A‐SCN10A” locus and effect the expression of SCN5A . Hey2 has been recently shown to be a BrS susceptibility gene by modulating cardiac transmural ion channel patterning and electrical heterogeneity . In addition, activation of canonical Wnt signaling has been shown to decrease SCN5A mRNA levels, Na v 1.5 protein and Na + current density in rat ventricular myocytes …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other transcriptomic approaches, such as coexpression analysis as recently implemented by us in a functional follow up study of a locus identified for Brugada syndrome, may also provide functional hypotheses to be tested experimentally. 20 The progress being made in recent years in dissecting genetic factors contributing to AF, both by means of genetic studies in large cohorts of AF 10 and by the intermediate phenotype approach, is remarkable. With their large collaborative study on P wave indices as intermediate phenotypes, Christophersen et al 6 have made another important contribution along a journey that will eventually lead us through the maze of AF.…”
Section: Tadros Et Almentioning
confidence: 99%